A performance evaluation of a new bitmap-based XML processing approach over RDBMS. (1st January 2012) - Al-Badawi, Mohammed; Ramadhan, Haider Ali; North, Siobhan; Eaglestorne, Barry
This paper presents a comprehensive performance analysis of PACD; a novel bitmap-based XML processing approach introduced earlier to resolve several performance issues identified in existing XML database technology. The study evaluated three performance aspects of XML database techniques including query processing, XML updates and scalability. Each of these aspects has been tested using various measures and compared with some representative alternative approaches. Despite its narrow domain for the order-access queries and its high cost in terms of the number IO-read operations, PACD almost performed well in terms of query processing, resource consumption during XML updates and has shown acceptable scalability over a variety of XML database categories.